In situ characterization of residual stress in glass-to-metal seal. Issue 16 (November 2019) - Hu, Kangjia; Yan, He; Fan, Zhichun; Diao, Xingzhong; Liu, Malin; Li, Shenhou; Zhang, Yong
Abstract: This study presents a new approach based on fiber Bragg grating (FBG) sensors toward measuring instantaneous and continuous changes of residual strain and stress in glass during glass-to-metal (GTM) sealing process. The GTM seal consists of three components which include stainless steel housing, borosilicate sealing glass and Kovar pin. The temperature cycle of sealing process was from room temperature (20 °C) to 880 °C, and then back to 20 °C. It was found that residual strain in glass increased rapidly at the glass transition region and gradually reached an asymptotic value with the decrease of temperature. The axial residual stress measured by the FBG sensor was 194.35 MPa at 20 °C. In addition, finite element modeling (FEM) was conducted to provide theoretical support. Stress modeling revealed that axial residual stress at the location of sensor was 145.47 MPa. The experimental determination of the residual stress is highly consistent with the theoretical calculation.